LOW-INVASIVE SURGERY OF DIFFUSE PERITONITIS COMPLICATED BY ABDOMINAL SEPSIS - N. I. Izimbergenov; A. S. Koishibaev; G. N. Izimbergenova; B. Zh. Karimova; K. S. Imanbaev; M. A. Saduov; B. M. Mukhamedgalieva (Вестник хирургии имени И.И. Грекова)
On the experience of treatment of 45 patients the efficacy of the programmed control sanation laparoscopy of the abdominal cavity was proved in postoperative period. This method had an advantage in comparison with open approach. Postoperative complications decreased from 50% to 28,8% (p